1984
DOI: 10.1111/j.1365-2141.1984.tb02941.x
|View full text |Cite
|
Sign up to set email alerts
|

The interpretation of platelet kinetic studies for the identification of sites of abnormal platelet destruction

Abstract: Summary. The kinetics of platelets labelled with 111In have been studied in a series of 175 subjects including 18 normal volunteers, and 12 patients with idiopathic thrombocytopenic purpura (ITP), but excluding patients in whom there was scintigraphic evidence of intravascular platelet consumption. From analysis of the kinetics, the following parameters were calculated: splenic blood flow (SBF), intrasplenic platelet transit time (t), splenic platelet pool capacity (expressed as a percentage of the total circ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
16
1

Year Published

1990
1990
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 23 publications
2
16
1
Order By: Relevance
“…Indium-labeled autologous platelet scanning (ILAPS), in which indium-111 labeled autologous platelets are infused into the patient and subsequent scintigraphy reveals the site of platelet clearance, 36 emerged as a promising predictor of splenectomy response in the 1980s but has not been widely adopted. …”
Section: Platelet Scintigraphymentioning
confidence: 99%
“…Indium-labeled autologous platelet scanning (ILAPS), in which indium-111 labeled autologous platelets are infused into the patient and subsequent scintigraphy reveals the site of platelet clearance, 36 emerged as a promising predictor of splenectomy response in the 1980s but has not been widely adopted. …”
Section: Platelet Scintigraphymentioning
confidence: 99%
“…the splenic blood flow and the intrasplenic platelet transit time. Finally, it has been demonstrated that the splenic platelet pool size and the splenic blood flow increase concomitantly with increasing spleen size, and that the splenic blood flow can be modulated by infusion of adrenaline and isoprenaline (26)(27)(28)(29).…”
Section: Kuttimentioning
confidence: 99%
“…It has been proposed that patients with purely or predominantly splenic sequestration determined by ILAPS may be more likely to respond to splenectomy than those exhibiting hepatic, mixed, or diffuse patterns. 4 To evaluate the potential of ILAPS to predict response to splenectomy, we performed a comprehensive literature review of all studies in which ILAPS was performed prior to splenectomy in patients with ITP.A search of the PubMed database limited to English language references was conducted by combining the MeSH (Medical Subject Heading) term "indium" with the keywords "ITP," "immune thrombocytopenic purpura," "idiopathic thrombocytopenic purpura," and "autoimmune thrombocytopenia" between 1950 and June 30, 2010. This strategy yielded 51 citations.…”
mentioning
confidence: 99%
“…It has been proposed that patients with purely or predominantly splenic sequestration determined by ILAPS may be more likely to respond to splenectomy than those exhibiting hepatic, mixed, or diffuse patterns. 4 To evaluate the potential of ILAPS to predict response to splenectomy, we performed a comprehensive literature review of all studies in which ILAPS was performed prior to splenectomy in patients with ITP.…”
mentioning
confidence: 99%